Reference frame selection in dialog: priming or preference? - Johannsen, Katrin; De Ruiter, Jan P. (Frontiers in Human Neuroscience, 2013)
We investigate effects of priming and preference on frame of reference (FOR) selection in dialogue. In a first study, we determine FOR preferences for specific object configurations to establish a baseline. In a second study, we focus on the selection of the relative or the intrinsic FOR in dialogue using the same stimuli and addressing the questions whether a) interlocutors prime each other to use the same FOR consistently or b) the preference for the intrinsic FOR predominates priming effects. Our results show effects of priming (more use of the relative FOR) and a decreased preference for the intrinsic FOR. However, as FOR selection did not have an effect on target trial accuracy, neither effect alone represents the key to successful communication in this domain. Rather, we found that successful communication depended on the adaptation of strategies between interlocutors: the more the interlocutors adapted to each other’s strategies, the more successful they were.